Preparation method and application of spherical molecular sieve adsorbent

Through the preparation method of spherical molecular sieve adsorbent, the problem of removing composite pollutants in acidic mine wastewater was solved, and efficient adsorption of Fe3+ and Cd2+ was achieved, demonstrating the acid resistance and mechanical strength of the material, and is suitable for complex water purification.

CN119114008APending Publication Date: 2024-12-13KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411180122.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat the composite pollutants in acidic mine wastewater, especially the removal of a variety of heavy metal ions, and the acid resistance and mechanical strength of the materials are insufficient.

Method used

By using the preparation method of spherical molecular sieve adsorbent, the alkali solution is added to the calcined kaolin, stirred and crystallized at high temperature, and then mixed with water glass and polyethylene glycol-600 solution, heated and calcined by water bath to prepare the Spherical molecular sieve adsorbent with high adsorption capacity.

Benefits of technology

It has achieved efficient adsorption of Fe3+ and Cd2+ in acidic mine wastewater, and the material is non-toxic and environmentally friendly. It is suitable for specific adsorption of composite pollutants, significantly improving the water purification effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114008A_ABST
    Figure CN119114008A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a spherical molecular sieve adsorbent, and belongs to the field of water treatment. The preparation method of the spherical molecular sieve adsorbent comprises the following steps: adding kaolin calcined in a muffle furnace into an alkali solution, and rapidly stirring the mixed solution for 2 hours to make the mixed solution uniform; the method comprises the following steps: mixing the molecular sieve powder with a mixed solution, aging the mixed solution at 60 DEG C for 4 hours, crystallizing the mixed solution at 105 DEG C for 24 hours, and filtering, cleaning and drying the mixed solution after the reaction is completed to obtain the molecular sieve powder. And crosslinking the molecular sieve powder with water glass to form a sphere, drying, and calcining in a muffle furnace for 4 hours to obtain the spherical molecular sieve. The molecular sieve prepared by the method has the characteristics of fast reaction, large adsorption capacity, reusability and the like. The method is non-toxic and environment-friendly, has high mechanical strength and acid resistance through simple mixing, and achieves the maximum removal rates of 98% and 99% for iron ions and cadmium ions respectively.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a spherical molecular sieve adsorbent and application thereof, and belongs to the field of water treatment. Background Art

[0002] At present, the research mainly focuses on the removal of single pollutants, and there is less research on the mechanism of action and treatment effect of coexisting pollution. However, most environmental problems are caused by multiple pollutants. Unlike single pollution, the environmental problems caused by compound pollution may be more complex and serious. Acid mine drainage has a low pH value, contains a large amount of soluble heavy metal ions, has high hardness, and sometimes even has color. The water quality is poor, the water volume is large, the pollution range is wide, the duration is long, the pollutant concentration is high, and it is difficult to treat. Therefore, in the process of treating acid mine drainage, it is necessary to consider the compound pollution of multiple heavy metals and the acid resistance and mechanical strength of the material. Therefore, it is necessary to develop an adsorbent that can adsorb multiple heavy metal ions. Summary of the invention

[0003] In order to obtain a method that can simultaneously adsorb Fe 3+ 、Cd 2+ One of the purposes of the present invention is to provide a method for preparing a spherical molecular sieve adsorbent, the specific preparation method comprising the following steps:

[0004] (1) Adding an alkaline solution to the calcined kaolin, stirring and aging the mixture, and then crystallizing the mixture at high temperature. After the reaction is completed, filtering, washing and drying the solution to obtain a molecular sieve powder.

[0005] (2) Molecular sieve powder, water glass and water are fully mixed and then dripped into polyethylene glycol-600 solution, and the obtained mixed solution is heated in a water bath.

[0006] (3) The material subjected to water bath heating treatment in step (3) is washed with deionized water, dried and then calcined to obtain a spherical molecular sieve adsorbent.

[0007] Preferably, in step (1), the mass ratio of kaolin to sodium hydroxide solution is 0.13-0.15, and the concentration of sodium hydroxide is 0.5-4.5 mol / L.

[0008] Preferably, in step (1), the calcination temperature is 550-850° C. and the time is 3-7 hours; the high temperature crystallization temperature is 90-110° C. and the time is 12-24 hours.

[0009] Preferably, in step (2), the mass ratio of the molecular sieve powder, water glass and water is 4:3.5:2 to 6:4:3; the mass ratio of the total mass of the molecular sieve powder, water glass and water to the polyethylene glycol-600 solution is 0.63 to 0.84.

[0010] Preferably, in step (3), the water bath heating temperature is 60-80° C., the time is 24 hours, the calcination temperature is 450-550° C., and the calcination time is 4 hours.

[0011] Another object of the present invention is to provide an application of a spherical molecular sieve adsorbent in adsorbing iron ions and cadmium ions in acidic mine wastewater.

[0012] Beneficial Effects of the Invention

[0013] The invention is non-toxic and environmentally friendly, and prepares spherical molecular sieve functional materials through simple mixing and cross-linking. It has specific adsorption sites corresponding to different pollutants, and is beneficial to removing complex pollutants in water bodies. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a SEM image of a spherical molecular sieve adsorbent preparation method and the material obtained in its application provided by the present invention.

[0015] Figure 2 This is a diagram for optimizing the material preparation conditions.

[0016] Figure 3 This is the fitting diagram of the kinetic model for the adsorption of iron and cadmium by the material.

[0017] Figure 4 This is a diagram showing the material's adsorption of a mixed solution of iron and cadmium.

[0018] Figure 5 XRD and FI-IR characterization diagrams of the materials.

[0019] Figure 6 This is the energy spectrum of the material before and after adsorption. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0021] Example 1

[0022] This example explores the effect of sodium hydroxide concentration on the adsorption effect of the adsorbent, and includes the following steps:

[0023] (1) Weigh 2 g, 6 g, 10 g, and 14 g of sodium hydroxide, respectively, and mix them with 100 mL of deionized water, and disperse them in water by ultrasonication to prepare 0.5 mol / l, 1.5 mol / l, 2.5 mol / l, and 3.5 mol / l sodium hydroxide solutions. Add 15 g of kaolin to each solution, stir the solution rapidly for 2 hours to make it uniformly mixed, age the mixed solution at 60° C. for 4 hours, and then crystallize the solution at 105° C. for 24 hours. Finally, after the reaction is completed, filter, wash, and dry the solution to obtain a molecular sieve powder.

[0024] (2) Weigh 4 g of the molecular sieve powder obtained in step (1), 3.5 g of water glass, and 2 g of water, mix them thoroughly, and then drop them into 50 mL of polyethylene glycol-600 solution using a syringe, and place them in a water bath at 80° C. for 24 hours.

[0025] (3) The material obtained in step (2) is washed with deionized water, placed in an oven for drying for 24 hours, and then placed in a muffle furnace for calcination for 4 hours to obtain a spherical molecular sieve.

[0026] Experimental process: Preparation of Fe 3+ The concentration is 100mg / L, Cd 2+ The concentration was 100 mg / L, and the pH was adjusted to 3 and 6; 0.25 g of each spherical molecular sieve was weighed and placed in a 100 mL ground-mouth conical flask, and Fe 3+ Concentration is 100mg / L or Cd 2+ The concentration was 100 mg / L; shaken at 25°C and 180 r / min for 24 hours.

[0027] The experimental results show that when the concentration of sodium hydroxide is 1.5 mol / l, the adsorption effect is better.

[0028] Example 2

[0029] This example explores the effect of crystallization time on a single system adsorption experiment, and includes the following steps:

[0030] (1) Weigh 6 g of sodium hydroxide, mix it with 100 mL of deionized water, and fully disperse it in water by ultrasonication to prepare a 1.5 mol / l sodium hydroxide solution. Add 15 g of kaolin to the solution, and stir the solution rapidly for 2 hours to make it uniformly mixed. Then, age the solution at 60° C. for 4 hours, and then crystallize the solution at 105° C. for 18 hours, 24 hours, 30 hours, and 36 hours. Finally, after the reaction is completed, filter, wash, and dry the solution to obtain a molecular sieve powder.

[0031] (2) Weigh 4 g of the molecular sieve powder obtained in step (1), 3.5 g of water glass, and 2 g of water, mix them thoroughly, and then drop them into 50 mL of polyethylene glycol-600 solution using a syringe, and place them in a water bath at 80° C. for 24 hours.

[0032] (3) The material obtained in step (2) is washed with deionized water, placed in an oven for drying for 24 hours, and then placed in a muffle furnace for calcination for 4 hours to obtain a spherical molecular sieve.

[0033] Experimental process: Preparation of Fe 3+ The concentration is 100mg / L, Cd 2+ The concentration was 100 mg / L, and the pH was adjusted to 3 and 6; 0.25 g of each spherical molecular sieve was weighed and placed in a 100 mL ground-mouth conical flask, and Fe 3+ Concentration is 100mg / L or Cd 2+ The concentration was 100 mg / L; shaken at 25°C and 180 r / min for 24 hours.

[0034] The experimental results show that when the crystallization time is 24 hours, the adsorption effect is better.

[0035] Example 3

[0036] This example explores the effect of crystallization temperature on a single system adsorption experiment, and includes the following steps:

[0037] (1) Weigh 6 g of sodium hydroxide, mix it with 100 mL of deionized water, and fully disperse it in water by ultrasonication to prepare a 1.5 mol / l sodium hydroxide solution. Add 15 g of kaolin to the solution, and stir the solution rapidly for 2 hours to make it uniformly mixed. Then, age the solution at 60°C for 4 hours, then crystallize the solution at 75°C, 90°C, 105°C, and 120°C for 24 hours. Finally, after the reaction is completed, filter, wash and dry the solution to obtain a molecular sieve powder.

[0038] (2) Weigh 4 g of the molecular sieve powder obtained in step (1), 3.5 g of water glass, and 2 g of water, mix them thoroughly, and then drop them into 50 mL of polyethylene glycol-600 solution using a syringe, and place them in a water bath at 80° C. for 24 hours.

[0039] (3) The material obtained in step (2) is washed with deionized water, placed in an oven for drying for 24 hours, and then placed in a muffle furnace for calcination for 4 hours to obtain a spherical molecular sieve.

[0040] Experimental process: Preparation of Fe 3+ The concentration is 100mg / L, Cd 2+ The concentration was 100 mg / L, and the pH was adjusted to 3 and 6; 0.25 g of each spherical molecular sieve was weighed and placed in a 100 mL ground-mouth conical flask, and Fe 3+Concentration is 100mg / L or Cd 2+ The concentration was 100 mg / L; shaken at 25°C and 180 r / min for 24 hours.

[0041] The experimental results show that when the crystallization temperature is 105℃, the adsorption effect is better.

[0042] Residual concentration determination method: The obtained solution was filtered and then Fe was determined by flame atomic force microscope. 3+ 、Cd 2+ of the residual concentration.

[0043] Example 4

[0044] See also Figure 1 to Figure 2 As shown, a method for preparing a spherical molecular sieve adsorbent and its application include the following steps:

[0045] (1) calcining kaolin at 550-850°C in a muffle furnace for 7h, dissolving 6g of sodium hydroxide in a beaker filled with deionized water to obtain a sodium hydroxide solution, adding the sodium hydroxide solution to the calcined kaolin, stirring and aging, and then high-temperature crystallizing the mixture at 105°C for 24h, filtering, washing and drying the solution to obtain a molecular sieve powder.

[0046] (2) Weigh 4 g of the molecular sieve powder obtained in step (1), 3.5 g of water glass, and 2 g of water, mix them thoroughly, and then drop them into 50 mL of polyethylene glycol-600 solution using a syringe, and place them in a water bath at 80° C. for 24 hours.

[0047] (3) The material obtained in step (3) is washed with deionized water, placed in an oven for drying for 24 hours, and then placed in a muffle furnace for calcination for 4 hours to obtain a spherical molecular sieve.

[0048] Example 5

[0049] An application of a spherical molecular sieve adsorbent, the specific steps are:

[0050] (1) Preparation of Fe 3+ and Cd 2+ The concentrations were all 100 mg / L, and the pH was adjusted with 1 M NaOH and 1 M HCl to 3 and 6, respectively;

[0051] (2) Weigh 0.25 g of the spherical molecular sieve material prepared in Example 4 and put it into a ground-mouth conical flask. Set up two parallel samples at different adsorption times;

[0052] (3) Pour 40 mL of the solution in (1) into (2) and place in a shaker. The shaking time is 0.5, 1, 3, 5, 7, 9, 15, 20, 25, 30, 35, 40 h, respectively, and the speed is 180 r / min;

[0053] The experimental results show that the spherical molecular sieve has a strong 3+ and Cd 2+ The adsorption basically reaches adsorption equilibrium after about 24 hours and 20 hours of contact.

[0054] Residual concentration determination method, Fe 3+ and Cd 2+ The specific determination content is: the obtained solution is filtered and then measured by flame atomic force measurement.

[0055] In order to further understand the adsorption process and adsorption mechanism, the pseudo-first-order kinetic equation, pseudo-second-order kinetic equation and intraparticle diffusion model (Weber-Morris model) were used to fit the kinetic data:

[0056] Pseudo-first-order kinetic equation:

[0057] qt=qe·(1-e-k1·t)

[0058] Pseudo-second-order kinetic equation:

[0059]

[0060] Among them, q t (mg·g-1) and q e (mg·g-1) are the adsorption amounts of the target pollutant at time t and at equilibrium, respectively. k1(min -1 ) and k2(g -1 mg -1 min -1 ) are the pseudo-first-order and pseudo-second-order kinetic adsorption rate constants, respectively.

[0061] Result analysis: Both cadmium and iron conform to pseudo-secondary kinetic adsorption, and the adsorption mechanism is chemical adsorption.

[0062] Example 6

[0063] A method for preparing a spherical molecular sieve adsorbent and its application, comprising the following steps:

[0064] (1) Prepare a solution with a concentration of 100 mg / L, Cd 2+ -Fe 3+ The concentration is 50mg / L+10mg / L, Cd 2+ -Fe 3+ The concentration is 50mg / L+30mg / L, Cd 2+ -Fe 3+ The concentration is 50mg / L+50mg / L, Cd 2+ -Fe 3+The concentration is 50mg / L + 60mg / L, and the pH is adjusted to 3 with 1M NaOH and 1M HCl;

[0065] (2) Weigh 0.25 g of the material prepared in Example 1 and put it into a ground-mouth conical flask. Set up two parallel samples under different concentration conditions;

[0066] (3) Pour 40 mL of the solution in (1) into (2), place in a shaker, and shake for 24 hours at a speed of 180 r / min;

[0067] The experimental results show that Fe 3+ For Cd 2+ The adsorption of Fe 3+ The increase in Cd concentration 2+ The removal rate will decrease, indicating that iron ions inhibit the removal of cadmium ions by the material. The two are in a competitive relationship, and the competitiveness of iron is greater than that of cadmium.

[0068] Residual concentration determination method, including determination of Fe 3+ and Cd 2+ The specific determination contents are as follows:

[0069] Determination of residual Fe by flame atomic absorption 3+ and Cd 2+ concentration.

[0070] Results Analysis

[0071] Depend on Figure 1 It can be seen that: Figure 1 (a) shows the surface morphology of the kaolin used in Example 4. It can be observed that the surface of the kaolin is in the form of flakes and particles that are irregularly stacked together. The surface is dense and it is not easy to form adsorption sites. Figure 1 (b) is an electron microscope image of the outer surface of calcined kaolin in Example 4, where many small pores can be seen on the surface. Figure 1 (c) It can be seen that the rough surface of the alkali-treated metakaolin in Example 4 is caused by the accumulation of particles after being corroded by the alkali. Figure 1 Figures (d) and (e) are electron microscope images of the molecular sieve in Example 4, where the polyhedral structure can be clearly seen. Figure (f) is the material of the powdered molecular sieve cross-linked with water glass in Example 4. Figures (g) and (h) are the materials of Example 5 after the adsorption of metal cadmium and iron. Figure (i) is a cross-sectional view of the spherical molecular sieve in Example 4.

[0072] Depend on Figure 2 It can be seen that the optimal material preparation conditions of the experimental molecular sieves of Examples 1 to 3 are: NaOH concentration of 1.5 mol / L, crystallization time of 24 hours, and crystallization temperature of 105°C.

[0073] Depend on Figure 3 It can be seen that the nonlinear fitting curves of the pseudo-first-order and pseudo-second-order equations in Example 5 are as follows Figure 3 As shown in the figure, it can be seen from the calculation that the correlation coefficient of pseudo-second-order kinetics (R 2 =0.998) is much higher than the correlation coefficient of the pseudo-first-order kinetic equation (R 2 =0.988), therefore, the pseudo-second-order kinetic model can better describe the adsorption process of iron and cadmium by molecular sieves.

[0074] Depend on Figure 4 It can be seen that in Example 6, in the mixed system of iron ions and cadmium ions, the cadmium ion concentration remains unchanged. As the iron ion concentration continues to increase, the cadmium ion removal rate decreases. The presence of iron ions inhibits the removal of cadmium ions by the material. The two are competitive for adsorption, and the competitiveness of iron ions is greater than that of cadmium ions.

[0075] Depend on Figure 5 It can be seen that: (a) is the XRD diagram of the material. The XRD diagrams of kaolin, calcined kaolin, alkali-treated metakaolin, molecular sieve powder, and spherical molecular sieves are compared with the standard PDF card. The characteristic peaks of P-type molecular sieves appear in molecular sieves and spherical molecular sieves, so P-type molecular sieves are successfully synthesized. Figure (b) is the FI-TR diagram of the material. It can be found that the strength of the functional group has changed after adsorption, indicating that the material has reacted with the metal.

[0076] Depend on Figure 6 It can be seen that: Figures (a), (b), and (c) are the energy spectra of the material in Example 5 before and after the adsorption of heavy metals cadmium and iron, respectively. The peaks of cadmium and iron appear in (b) and (c), indicating that the material has successfully adsorbed metal cadmium and iron.

[0077] The above phenomenon shows that the present invention is non-toxic and environmentally friendly, and the spherical molecular sieve functional material is prepared by simple mixing and cross-linking.

[0078] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that a specific feature, structure, material or characteristic described in conjunction with the embodiment or example is included in at least one example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0079] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a spherical molecular sieve adsorbent, characterized in that: The specific preparation method comprises the following steps: (1) adding an alkaline solution to the calcined kaolin, stirring and aging the mixture, and then crystallizing the mixture at high temperature. After the reaction is completed, filtering, washing and drying the solution to obtain a molecular sieve powder; (2) Molecular sieve powder, water glass and water are fully mixed and then dripped into polyethylene glycol-600 solution, and the obtained mixed solution is heated in a water bath; (3) The material subjected to water bath heating treatment in step (3) is washed with deionized water, dried and then calcined to obtain a spherical molecular sieve adsorbent.

2. The method for preparing a spherical molecular sieve adsorbent according to claim 1, characterized in that: The mass ratio of kaolin to sodium hydroxide solution in step (1) is 0.13-0.15, and the concentration of sodium hydroxide is 0.5-4.5 mol / L.

3. The method for preparing a spherical molecular sieve adsorbent according to claim 1, characterized in that: In step (1), the calcination temperature is 550-850° C. and the time is 3-7 hours; the high temperature crystallization temperature is 90-110° C. and the time is 12-24 hours.

4. The method for preparing a spherical molecular sieve adsorbent according to claim 1, characterized in that: In step (2), the mass ratio of molecular sieve powder, water glass and water is 4:3.5:2-6:4:3; the mass ratio of the total mass of molecular sieve powder, water glass and water to the mass ratio of polyethylene glycol-600 solution is 0.63-0.

84.

5. The method for preparing a spherical molecular sieve adsorbent according to claim 1, characterized in that: In step (3), the water bath heating temperature is 60-80° C., the time is 24 hours, the calcination temperature is 450-550° C., and the calcination time is 4 hours.

6. Use of the spherical molecular sieve adsorbent prepared by the method according to any one of claims 1 to 5 in the adsorption of iron ions and cadmium ions in acidic mine wastewater.